Aspiration therapy leads to weight loss in obese subjects: a pilot study - Sullivan, Shelby; Stein, Richard; Jonnalagadda, Sreenivasa; Mullady, Daniel; Edmundowicz, Steven (Gastroenterology (New York, N.Y. 1943), 2013)
Obese patients rarely achieve long-term weight loss with only lifestyle interventions. We evaluated the use of endoscopic aspiration therapy for obesity. Aspiration therapy involves endoscopic placement of a gastrostomy tube (A-Tube) and the AspireAssist siphon assembly (Aspire Bariatrics, King of Prussia, PA) to aspirate gastric contents 20 minutes after meal consumption. We performed a pilot study of 18 obese subjects who were randomly assigned (2:1) to groups that underwent aspiration therapy for 1 year plus lifestyle therapy (n = 11; mean body mass index, 42.6 ± 1.4 kg/m(2)) or lifestyle therapy only (n = 7; mean body mass index, 43.4 ± 2.0 kg/m(2)). Lifestyle intervention comprised a 15-session diet and behavioral education program. Ten of the 11 subjects who underwent aspiration therapy and 4 of the 7 subjects who underwent lifestyle therapy completed the first year of the study. After 1 year, subjects in the aspiration therapy group lost 18.6% ± 2.3% of their body weight (49.0% ± 7.7% of excess weight loss [EWL]) and those in the lifestyle therapy group lost 5.9% ± 5.0% (14.9% ± 12.2% of EWL) (P < .04). Seven of the 10 subjects in the aspiration therapy group completed an additional year of therapy and maintained a 20.1% ± 3.5% body weight loss (54.6% ± 12.0% of EWL). There were no adverse effects of aspiration therapy on eating behavior and no evidence of compensation for aspirated calories with increased food intake. No episodes of binge eating in the aspiration therapy group or serious adverse were reported. In a pilot study, aspiration therapy appears to be a safe and effective long-term weight loss therapy for obesity.